2013
DOI: 10.1080/03079457.2013.852157
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigations on the role of clinically healthy racing pigeons as a reservoir for avian paramyxovirus-1 and avian influenza virus

Abstract: Clinically healthy racing pigeons may harbour notifiable pathogens and serve as an unnoticed reservoir. Thus, 3480 healthy racing pigeons from 172 different lofts were monitored over a period of 2 years for the presence of avian influenza virus (AIV) and avian paramyxovirus-1 (APMV-1). Pharyngeal and cloacal swabs as well as blood samples were collected from juvenile and adult pigeons. Pools of five pharyngeal swabs per loft and age group were initially screened by real-time reverse transcriptase-polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…Although several reports described the isolation of avian influenza virus from pigeons or the detection of different subtypes of influenza virus by RT-PCR (Gronesova et al, 2009;Mansour et al, 2014), the majority of the studies showed that pigeons are generally resistant to avian influenza virus replication and are not likely to be a major reservoir and transmission host for avian influenza virus (Liu et al, 2007;Kohls et al, 2011;Smietanka et al, 2011;Yamamoto et al, 2012;Teske et al, 2013;Kalthoff et al, 2014;PantinJackwood et al, 2014). Here, we investigated the susceptibility of pigeons to avian H7N9 subtype.…”
Section: Discussionmentioning
confidence: 95%
“…Although several reports described the isolation of avian influenza virus from pigeons or the detection of different subtypes of influenza virus by RT-PCR (Gronesova et al, 2009;Mansour et al, 2014), the majority of the studies showed that pigeons are generally resistant to avian influenza virus replication and are not likely to be a major reservoir and transmission host for avian influenza virus (Liu et al, 2007;Kohls et al, 2011;Smietanka et al, 2011;Yamamoto et al, 2012;Teske et al, 2013;Kalthoff et al, 2014;PantinJackwood et al, 2014). Here, we investigated the susceptibility of pigeons to avian H7N9 subtype.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, marble spleen disease caused by siadenovirus has already been described as a common disease in pheasants raised on farms but not yet in free-ranging individuals (Fitzgerald et al 1992;Fitzgerald and Reed 1989;Pennycott 2000). The disease occurs naturally in pheasants 3-8 months of age (Swayne 2013). Characteristic pathomorphological lesions are splenomegaly associated with yellow and gray-white spots on the spleen's surface resulting in the characteristic marble-like look (Orlic et al 2003), but normal appearance of spleen can also occur (Pennycott 2000;Pennycott 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic pathomorphological lesions are splenomegaly associated with yellow and gray-white spots on the spleen's surface resulting in the characteristic marble-like look (Orlic et al 2003), but normal appearance of spleen can also occur (Pennycott 2000;Pennycott 2001). Other typical gross lesions are oedematous congested lungs (Fitzgerald and Reed 1989;Swayne 2013). Data about the occurrence of infectious bursal disease in pheasants are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…from pigeons, direct transmission to humans has not yet been reported (Haag-Wackernagel and Moch 2004). On the basis of their studies regarding the adhesion and invasion models, Teske et al (2013) suggested that pigeon-derived C. jejuni isolates were capable of infecting human enterocytes and producing the virulence factor cytolethal-distending toxin.…”
Section: Discussionmentioning
confidence: 99%
“…A review of health hazards caused by feral pigeons reported one single case of S. enterica serotype Kiambu infection in man (Haag Wackemagel and Moch 2004). In a two-year study carried out on racing pigeons, Teske et al (2013) reported a range from a minimum of 0.9 to 3.7% of the positive lots investigated. In older studies (Vindevogel and Duchatel, 1979) the incidence of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%